2019
DOI: 10.1002/ajhb.23371
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the gut microbiota of Nicaraguan children in a water insecure context

Abstract: Objectives: The gut microbiota varies across human populations. The first years of life are a critical period in its development. While delivery mode and diet contribute to observed variation, the additional contribution of specific environmental factors remains poorly understood. One factor is waterborne enteric pathogen exposure. In this pilot study, we explore the relationship between household water security and the gut microbiota of children.Methods: From Nicaraguan households (n = 39), we collected drink… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 77 publications
(102 reference statements)
0
13
2
Order By: Relevance
“…Poor water quality, particularly water contaminated by enteric pathogens, may be an important factor shaping the colonization of the gut in early development. A study in Nicaragua found that infants and young children living in households with higher concentrations of total coliforms in their drinking water had lower ɑ-diversity and a greater relative abundance of potentially predatory or pathogenic bacteria in fecal samples relative to those using low-coliform water sources ( 209 ). This suggests that exposure to poor-quality water may render the gut more susceptible to harmful bacteria ( 210 ).…”
Section: Current Status Of Knowledgementioning
confidence: 99%
“…Poor water quality, particularly water contaminated by enteric pathogens, may be an important factor shaping the colonization of the gut in early development. A study in Nicaragua found that infants and young children living in households with higher concentrations of total coliforms in their drinking water had lower ɑ-diversity and a greater relative abundance of potentially predatory or pathogenic bacteria in fecal samples relative to those using low-coliform water sources ( 209 ). This suggests that exposure to poor-quality water may render the gut more susceptible to harmful bacteria ( 210 ).…”
Section: Current Status Of Knowledgementioning
confidence: 99%
“…One study measured water quality and the gut microbiome among water insecure households in Nicaragua. This study found that children from households with worse water quality had significantly less gut microbial diversity than children from households with better water quality (Piperata et al, 2020). In fact, this dysregulation of the gut microbiome in early life due to microbial contamination can lead to diarrheal disease, stunting, and potentially obesity later in life, thereby leading to a triple burden of disease (Daily et al, 2019; Guerrant et al, 2013).…”
Section: Human Biology Implications Of Water Insecuritymentioning
confidence: 99%
“…Schell () draws on his long‐term research with the Akwesasne Mohawk Nation in developing a biocultural framework for understanding the impact of PCB contamination on water security in these indigenous communities. Papers by Piperata et al (), Thompson et al (), Brewis et al () and Schuster et al () explore the influence of water insecurity on diverse aspects of nutritional health, ranging from the gut microbiome in children to infant feeding strategies, and the dual nutritional burden. In turn, the contributions by Houck et al () and Dinkel et al () examine the impact water quality and availability on infectious disease risks.…”
Section: Special Issue On Water and Human Biologymentioning
confidence: 99%